Photocatalytic Desulfonylative Homocoupling of Benzylic Sulfone Derivatives - Ohkura, Ryusei; Ohtsuka, Motoo; Yim, Jacky C.-H.; Nambo, Masakazu; Crudden, Cathleen M. (Synlett, 2022)
A desulfonylative homocoupling of benzylic sulfone derivatives through a photoredox Ir catalyst is described. The 3,5-bis(trifluoromethyl)phenyl group is an effective substituent on sulfonyl group in this reaction, providing the structurally diverse multiply arylated ethanes in good yields. The α-deuterated or α-fluorinated sulfones, which can be readily prepared by α-functionalization, were also applicable, highlighting an avenue to synthesize medicinally important structures.
Keywords: desulfonylative homocoupling; sulfone; photoredox catalysis; multiply arylated alkanes; carbon–sulfonyl bond activation